2014
DOI: 10.1017/cbo9780511894664
|View full text |Cite
|
Sign up to set email alerts
|

Automated Evaluation of Text and Discourse with Coh-Metrix

Abstract: Coh-Metrix is among the broadest and most sophisticated automated textual assessment tools available today. Automated Evaluation of Text and Discourse with Coh-Metrix describes this computational tool, as well as the wide range of language and discourse measures it provides. Part I of the book focuses on the theoretical perspectives that led to the development of Coh-Metrix, its measures, and empirical work that has been conducted using this approach. Part II shifts to the practical arena, describing how to us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
562
0
26

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 562 publications
(655 citation statements)
references
References 158 publications
6
562
0
26
Order By: Relevance
“…T-Scan (http:// languagelink.let.uu.nl/tscan) is one of the most elaborated solutions as it considers multiple features, including [20]: lexical and sentence complexity, referential cohesion and lexical diversity, relational coherence, concreteness, personal style, verbs and time, verbs and time, as well as probability features, all derived from Coh-Metrix [21][22][23]. Besides T-Scan, various Dutch surface tools have been reported that provide lexical indices for text difficulty, as well as recommendations to reorganize the text: e.g., Texamen, Klinkende Taal and Accessibility Leesniveau Tool [24].…”
Section: State Of the Artmentioning
confidence: 99%
“…T-Scan (http:// languagelink.let.uu.nl/tscan) is one of the most elaborated solutions as it considers multiple features, including [20]: lexical and sentence complexity, referential cohesion and lexical diversity, relational coherence, concreteness, personal style, verbs and time, verbs and time, as well as probability features, all derived from Coh-Metrix [21][22][23]. Besides T-Scan, various Dutch surface tools have been reported that provide lexical indices for text difficulty, as well as recommendations to reorganize the text: e.g., Texamen, Klinkende Taal and Accessibility Leesniveau Tool [24].…”
Section: State Of the Artmentioning
confidence: 99%
“…The indices are categorized into nine measures. As it takes too much space to explain all these indices in detail here, the interested readers are referred to [33].…”
Section: Readability Of Spanish Textsmentioning
confidence: 99%
“…In contrast to non-narrative texts, narrative texts are written on more familiar topics, using oral language and more familiar words and world knowledge [33]. The higher the grade level of the text, the lower the narrativity index will be [19].…”
Section: Readability Of Spanish Textsmentioning
confidence: 99%
See 2 more Smart Citations